Dayah Mudi Mesra Samalanga Bireuen Education Management - Zulfikar; M. Afif Zamroni (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
This research is raised based on the importance of the existence of Dayah in modern era which gived the opportunities for decresing the morals of the younger generation. So that, the existence of Dayah must be repaired from various aspect including education management. Therefore, with good management, it will provide output for students who are competent and have noble character. For this reason, the role of the management Dayah Mudi Mesra Samalanga greatly contributes for young generation and has a positive impact on the community around the dayah regarding improving the management of Islamic education in Indonesia. This research uses descriptive qualitative methods by describing phenomena that occur in the field and analyzed using existing theories. The results show that the planning at Dayah Mudi Mesra was very good by holding formative meetings at the beginning of the Hijriyah year, the organization of management is very good as evidenced by the division of performance and responsibilities of each team according to their abilities, implementation of management is very good according to the initial planning of the meeting formation, and supervision can also be carried out properly by knowing weaknesses and obstacles so that they can be used as evaluation material for the coming year.